Pendidikan, Pelatihan, Pengalaman, dan Penggunaan Informasi Akuntansi dalam Pembuatan Laporan Keuangan pada UKM di Kota Bengkulu - Isma Coryanata (Jurnal Akuntansi, 2016)
In conducting the entire business activity, small businesses can not be separated from the operating result(profit) enterprises in the previous period. To determine the end of each period's operating results can be seen from thefinancial statements prepared by the small businessman. By knowing the operating results (profits) is, theseentrepreneurs can perform management and better funding. But the reality on the ground is still a lot of small businessesthat do not make financial statements. The purpose of this study is to empirically examine the influence of individualcapacity and use of accounting information to the preparation of financial statements of small business in the city ofBengkulu. The sampling method in this research using random sampling of 100 small business in the city of Bengkulu.Hypothesis testing using multiple regression analysis. The test results indicate that there are influence the capacity ofindividuals and the use of accounting information to financial statements for small business in the city of Bengkulu.Keywords: education, training, experience, the use of accounting information, financial statements, small business